The nexus between Geography teachers’ code-switching perceptions and practices: A case study (Interdisciplinary Journal of Education Research, 2024)
The study investigated the intersection between teachers' perceptions of code-switching and their actual code-switching practices. The research focused on four Grade 10-12 Geography teachers who were selected purposefully based on their qualifications, teaching experience, fluency in, or familiarity with, the two languages involved, and the grade level they taught. Following the interpretive paradigm and qualitative approach, the study employed semi-structured interviews to gather the participants' perceptions of code-switching as a teaching practice, as well as their implementation of it in the classroom. Additionally, classroom observations were conducted to observe the teachers' actual code-switching practices during Geography lessons. The study then compared the teachers' perceptions and practices to determine the extent of their intersection. Thematic data analysis was used to analyse the data. The results revealed a discrepancy between the teachers' perceptions and practices, particularly in terms of the purposes, types, and frequency of code-switching, among other aspects. The study concludes that classroom code-switching was not a deliberate and conscious activity guided by a well-informed and equally conscious understanding of the practice, but rather a largely habitual behaviour. As a recommendation, the study suggests conducting in-service workshops to enhance teachers' comprehension of code-switching and provide them with effective strategies for its application in the classroom.
Keywords: Code-switching practice; multilingualism; teachers’ perceptions; teachers’ practices; Geography teachers